3D printing and the future retail supply chain - Armbruster, Christoph (2017)
Nowadays, the development of innovative technologies to satisfy individual consumer needs is vital for successful companies. Since several years additive manufacturing attains high media attention as a new paradigm of value creation for various industries. This paper studies 3D printing and the possible applications in the retail industry shaping new supply chain strategies. The concept of 3D printing and the state-of--the-art retail supply chain will be examined and potential benefits of the implementation of 3D printing displayed. Furthermore, a scenario is developed and a new supply chain concept will be derived to shape the retail supply chain of the future.